2016
DOI: 10.1101/055921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription factors GAF and HSF act at distinct regulatory steps to modulate stress-induced gene activation

Abstract: 23The coordinated regulation of gene expression at the transcriptional level is fundamental to 24 organismal development and homeostasis. Inducible systems are invaluable when studying 25 transcription because the regulatory process can be triggered instantaneously, allowing the 26 tracking of ordered mechanistic events. Here, we use Precision Run-On sequencing (PRO-seq) 27 to examine the genome-wide Heat Shock (HS) response in Drosophila and the function of two 28 key transcription factors on the immediate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 75 publications
3
71
1
Order By: Relevance
“…Previous studies on the promoters of heat shock genes have identified a number of cis elements and corresponding factors-including SP1 in mammals and GAGA factor in Drosophila-that alter chromatin structure and affect the inducibility of heat-shock gene transcription (Morgan 1989;Tsukiyama et al 1994;Martinez-Balbas et al 1995;Duarte et al 2016). Binding of these factors at heat-shock gene promoters does not lead to the constitutive recruitment of HSF1 but rather directs nucleosome displacement to create DNA accessibility at HSEs for binding of HSF1 upon heat shock (Guertin and Lis 2010;Fuda et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the promoters of heat shock genes have identified a number of cis elements and corresponding factors-including SP1 in mammals and GAGA factor in Drosophila-that alter chromatin structure and affect the inducibility of heat-shock gene transcription (Morgan 1989;Tsukiyama et al 1994;Martinez-Balbas et al 1995;Duarte et al 2016). Binding of these factors at heat-shock gene promoters does not lead to the constitutive recruitment of HSF1 but rather directs nucleosome displacement to create DNA accessibility at HSEs for binding of HSF1 upon heat shock (Guertin and Lis 2010;Fuda et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Upon heat shock and the appearance of misfolded proteins, HSF1 is converted from an inert monomer to a functional DNA-binding trimer that binds selectively to heat-shock elements (HSEs) located within target promoters (Perisic et al 1989;Baler et al 1993). HSF1 then interacts with general transcription factors and coactivators to robustly induce transcription at both initiation and elongation steps (Mason and Lis 1997;Yuan and Gurley 2000;Park et al 2001;Duarte et al 2016). The activity of HSF1 is strongly influenced by posttranslational modifications and association with chaperones that regulate different steps of the HSR (Shi et al 1998;Westerheide et al 2009;Raychaudhuri et al 2014;Kourtis et al 2015).…”
mentioning
confidence: 99%
“…The Similar to the distinct mechanisms at play in pausing Pol II at M1BP-and GAF-controlled promoters (Li & Gilmour, 2013;Duarte et al, 2016), these data suggest that distinct mechanisms of release of paused Pol II exist at the two classes of poised Pol II promoters: additional factors that are not present in S2 cells are likely required to permit Hox-induced productive transcription at GAF-controlled promoters since we find little evidence that AbdA binding affects Pol II pausing, whereas at M1BP-controlled genes, AbdA binding is sufficient to increase gene transcription through the release of paused Pol II. The EMBO Journal Hox and M1BP cooperate to regulate transcription Amel Zouaz et al and histone marks in S2 cells, we found that the M1BP-and GAFpoised Pol II promoters targeted by AbdA were enriched for PcG proteins and H3K4me3 (Fig EV4).…”
Section: Hox Proteins Partner With the Pausing Factor M1bp To Fine Tumentioning
confidence: 98%
“…However, given that the majority of genes controlled by M1BP do not have distal enhancers (Zabidi et al, 2015), it is unlikely that this is the case for M1BP-targeted promoters. Both GAF and M1BP are important and distinct Drosophila Pol II pausing factors (Li & Gilmour, 2013;Fuda et al, 2015;Duarte et al, 2016), a role that proved important in understanding the nature of promoters targeted by AbdA and Ubx, since the majority of all promoters targeted by the Hox proteins contained poised Pol II (for example, see Figs 2B and 7A). GAF binding sites have previously been shown enriched at Ubx targets (Agrawal et al, 2011;Shlyueva et al, 2016), although a link between Hox and GAF in regulating gene transcription was not demonstrated.…”
Section: Hox Proteins Partner With the Pausing Factor M1bp To Fine Tumentioning
confidence: 99%
“…Transcriptional mechanisms of the HSR have been extensively studied. In Drosophila, GAGA-associated factor constitutively binds to the HSP70 promoter, which allows for the establishment of an open chromatin environment and paused Pol II at the promoterproximal region (Jonkers & Lis, 2015;Duarte et al, 2016). In response to heat shock, trimerized HSF quickly occupies HSEs in the promoter (Guertin & Lis, 2010).…”
Section: Introductionmentioning
confidence: 99%